Investigation of GEM-Micromegas detector on X-ray beam of synchrotron radiation - 张余炼 祁辉荣 胡碧涛 范胜男 王波 刘梅 张建 刘荣光 常广方 刘鹏 欧阳群 陈元柏 伊福廷 (Chinese physics C, 2014)
To reduce the discharge of the standard bulk Micromegas and GEM detectors, a GEM-Micromegas detector was developed at the Institute of High Energy Physics. Taking into account the advantages of the two detectors, one GEM foil was set as a preamplifier on the mesh of Micromegas in the structure and the CEM pream- plification decreased the working voltage of Micromegas to significantly reduce the effect of the discharge. At the same gain, the spark probability of the GEM-Micromegas detector can be reduced to a factor 0.01 compared to the standard Micromegas detector, and an even higher gain could be obtained. This paper describes the performance of the X-ray beam detector that was studied at 1W2B Laboratory of Beijing Synchrotron Radiation Facility. Finally, the result of the energy resolution under various X-ray energies was given in different working gases. This indicates that the GEM-Micromegas detector has an energy response capability in an energy range from 6 keV to 20 keV and it could work better than the standard bulk-Micromegas.